2021
DOI: 10.33086/ijmlst.v3i1.1850
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Parasites in Soil with The Existence of Parasites on Farmer's Nails

Abstract: Worms is an infectious disease caused by parasitic worms that can endanger health. Worms that often infect and have a very detrimental impact are soil-borne worm infections or Soil-Transmitted Helminths. Soil-Transmitted Helminths still considered insignificant because it is considered not to cause harm or cause death. This study aims to determine the relationship of parasites in the soil with the presence of parasites on the nails of farmers Sumber Urip 1 Village Wonorejo, East Java, Indonesia. The research m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Research has shown a relationship between the use of personal protective equipment and the prevalence of worm infections, confirming the importance of using PPE (Baidowi et al, 2019). It will protect a person or isolate part or all of the body from potential workplace hazards of disease (Wikurendra et al, 2021). Incomplete use of PPE can allow infectious eggs or larvae to enter various body organs such as hands, feet, and mouth.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Research has shown a relationship between the use of personal protective equipment and the prevalence of worm infections, confirming the importance of using PPE (Baidowi et al, 2019). It will protect a person or isolate part or all of the body from potential workplace hazards of disease (Wikurendra et al, 2021). Incomplete use of PPE can allow infectious eggs or larvae to enter various body organs such as hands, feet, and mouth.…”
Section: Discussionmentioning
confidence: 95%
“…This fecal examination is the standard gold examination for diagnosing helminthiasis, as the STH worm group with such a life cycle is well suited to provide a supportive diagnosis using fecal examination materials (Mahartina et al, 2020;Steinbaum et al, 2017). However, according to previous studies, worm eggs can also be found in nail clipping examinations (Tuuk et al, 2020;Wikurendra et al, 2021). In addition, identifying a miner's worm parasitic eggs can be used to know if STH has contaminated the environment (Wikurendra et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Penelitian Kofle et al (2017) di Bhaktapur menemukan cemaran parasit cacing di tanah 49,01% dengan Ascaris lumbricoides paling banyak diikuti Strongyloides stercoralis dan protozoa Giardia spp. Penelitian parasit di tanah dan keberadaan parasit pada kuku petani di desa Sumber Urip ditemukan 66,7% larva cacing tambang dan telur cacing nematoda, sedangkan 61,6% larva Ancylostoma duodenale pada kuku petani (Edza et al, 2021). Penelitian Paller dan Babia-Abion (2019) di Filipina menemukan bahwa penggunaan pupuk kandang dan air cucian mempunyai hubungan positif dengan cemaran parasit di dalam tanah.…”
Section: Pendahuluanunclassified